Novel ELISA based on fluorescent quenching of DNA-stabilized silver nanoclusters for detecting E. coli O157:H7. (30th May 2019) - Wang, Chun; Xing, Keyu; Zhang, Ganggang; Yuan, Meifang; Xu, Shaolan; Liu, Daofeng; Chen, Wenyao; Peng, Juan; Hu, Song; Lai, Wei-Hua
Highlights: ssDNA was designed that contains the appended block and anchoring block. An ELISA was established via fluorescent quenching of AgNCs by using sandwich-model. Fluorescence intensity change of AgNCs was used to detect E. coli O157:H7. This method showed specificity and reproducibility and could be used in food samples. Abstract: Escherichia coli O157:H7 ( E. coli O157:H7) is a potential threat to human health; thus, a rapid and sensitive method for detecting it is necessary. We designed a single-stranded DNA that contained an appended block and anchoring block. The appended block acted as a scaffold to prepare fluorescent Ag nanoclusters (AgNCs). The anchoring block contained Poly A, which bound with the surface of gold nanoparticles to quench the fluorescence of AgNCs. An interesting ELISA approach for detecting E. coli O157:H7 was established via fluorescent quenching of DNA-stabilized AgNCs by using a sandwich complex. The changes in fluorescence intensity of AgNCs were used to quantitatively detect E. coli O157:H7. The sensitivity for detecting E. coli O157:H7 reached 1.905 × 10 3 CFU/mL with a good linear range. Compared with conventional ELISA, the sensitivity of this technique increased by 30-fold. Moreover, this method demonstrated specificity and reproducibility and could be used in food samples.